Forming the image of powerful structures through political advertising in Russia - Nataliya Sergeevna Shkurko, Natalya Rinatovna Balynskaya,; Liliya Muhametovna Rahimova, Margarita Vladimirovna Kuznetsova, Natalia Stanislavovna Ivashina,; Darya Sergeyevna Buzhinskaya, Albina Muratzhanovna Maximova, (Opción, 2019)
The purpose of this article is to substantiate components of the image of powerful structures in Russia as objects of political advertising. Using a terminological analysis, this study outlines the essence of political advertising and image. As a result, the program and ideological component of the political image is the main one, since it reflects the meaning of the creation and activities of powerful structures. In conclusion, the reflection of all components of the image ensures the effectiveness of political advertising